A Study on Low Cost Microcontrollers for Converter Applications - zulkifli, shamsul aizam (International Journal of Electrical Engineering and Applied Sciences (IJEEAS), 2019)
In this project, the development of a control system based on single phase inverter in hardware and simulation have been conducted to study the use of low-cost microcontroller for converter application. Therefore, this project aims to develop a voltage control system that can be designed in Raspberry Pi and Arduino to understand the effectiveness of the microcontrollers. The inverter voltage is being controlled using Pulse Width Modulation (PWM) that is modelled using a feedback control using the MATLAB Simulink as a code generation. At the meantime, the Proportional (P) control has been used for the inverter output control in order the output voltage to follow the target reference value. This study has been divided into two stages where the MATLAB simulation has been developed for determined the control response for the single-phase inverter when using the Raspberry PI and Arduino as the source generation. After it has been successfully designing deed, the hardware has been set up to see the operation of the inverter with the voltage control that has been built in the MATLAB, by connecting to a resistive load as to represent any household applications such as a fluorescent lamp. The results show that, by using these low-cost microcontrollers, the controller is more accessible to be developed in the MATLAB and able to respond well to the hardware.